1989
DOI: 10.1021/bi00447a032
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-reduction potentials and ionization states of extracellular peroxidases from the lignin-degrading fungus Phanerochaete chrysosporium

Abstract: The oxidation-reduction potentials of lignin peroxidase isozymes H1, H2, H8, and H10 as well as the Mn-dependent peroxidase isozymes H3 and H4 are reported. The potentiometric titrations involving the ferrous and ferric states of the enzyme had Nernst plots indicating single-electron transfer. The Em7 values of lignin peroxidase isozymes H1, H2, H8, and H10 are -142, -135, -137, and -127 mV versus standard hydrogen electrode, respectively. The Em7 values for the Mn-dependent peroxidase isozymes H3 and H4 are -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
55
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 55 publications
13
55
0
Order By: Relevance
“…∆E p increased (up to 140-150 mV for scan rates of 500 mV\s), indicating the occurrence of quasi-reversibility. Figure 2 shows the pH-dependence of the redox potential for wt MnP, and the data at pH 7n0 agree with those already reported [23]. The data clearly showed that its redox behaviour was functionally modulated by the protonation of (at least) two groups, whose pK b values were redox-linked.…”
Section: Figure 2 Ph-dependence Of the Redox Potential E For Wt Mnpsupporting
confidence: 78%
See 1 more Smart Citation
“…∆E p increased (up to 140-150 mV for scan rates of 500 mV\s), indicating the occurrence of quasi-reversibility. Figure 2 shows the pH-dependence of the redox potential for wt MnP, and the data at pH 7n0 agree with those already reported [23]. The data clearly showed that its redox behaviour was functionally modulated by the protonation of (at least) two groups, whose pK b values were redox-linked.…”
Section: Figure 2 Ph-dependence Of the Redox Potential E For Wt Mnpsupporting
confidence: 78%
“…( \A #)! ), and the concentration was determined using an absorption coefficient, ε l 127 mM −" :cm −" at 407 nm [23]. Modified PG electrodes were prepared as previously described [24].…”
Section: Experimental Expression and Purificationmentioning
confidence: 99%
“…One of the key factors in evaluating the technological feasibility of these environmentally acceptable bio-bleaching systems is the stability of the peroxidases, particularly at high pH. Unfortunately, LiP has an extremely narrow pH optimum (pH 2.7-3.0) with respect to the majority of its substrates, and rapidly converts into a denatured species at pH 7.5 [23], particularly at elevated temperatures [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The lignin peroxidases are somewhat unique in that they have higher oxidation potentials (--1.35 V) than do most peroxidases (--0.8 V) (7). In this way these enzymes have a somewhat greater range of chemicals that they can oxidize; however this does not explain why so many chemicals are oxidized by these fungi.…”
mentioning
confidence: 95%